Analisa Pengaruh Kualitas Produk dan Promosi terhadap Keputusan Pembelian Kartu Tri: (Studi Kasus pada Mahasiswa STIE HAS Bukittinggi) - Siska, Adilla Juita; Jonea, Evan (Jurusan PIPS FKIP UMMY Solok, 2020)
The purpose of this research was to determine The Effect of Product Quality and Promotion to Decision Purchase The Tri Card. This research is a quantitative research using descriptive methods. Data sources used are data Primary and data Secondary. Data collection techniques in this study using a questionnaire. The study population were the student of STIE HAS Bukittinggi department of management reguler morning, afternoon, and Saturday Sunday year 2016, 2017, and 2018 and the sample will be taken as many as 74 people who took the technique sampling based on the slovin formula. The data analysis method used is instrument test namely a Test Validity and test Reliability, Test of Regression Model and Descriptive Variable Analysis (TCR). Data were analyzed using logistic binary regression. The results showed (1) The product positively affects and significance to decision purchase the Tri card. (2) Promotion positively affect and significance to decision purchase the Tri card.